Kualitas Pelayanan dan Sistem Manajemen SDM Toko Listrik Dan Eliktronik, Sinar Welisa Jaya Surabaya, Jawa Timur: Laporan Kegiatan Kuliah Kerja Lapangan - Ahen Nikolas Banoet; Harsono Teguh; Achmad Daengs GS (Universitas 45 Surabaya, 2024)
Companies really need competent and quality human resources, especially in this era of globalization. All business organizations must be ready to adapt and strengthen themselves in order to compete so that they are able to answer all challenges in the future. Human resources in this case are employees who always play an active and dominant role in every organizational activity because humans are planners, actors and determinants of the realization of goals. Human resource management (HRM) is a process of dealing with various problems within the scope of employees, employees, workers, managers and other workers to be able to support the activities of an organization or company in order to achieve predetermined goals. Human resources are a very valuable factor, so the company is responsible for maintaining the quality of work life and developing the workforce so that they are willing to contribute optimally to achieve company goals (Pruijt, 2003). Placing employees in the right positions will help the company to obtain optimal work results and achieving expected goals. This is reinforced by Hasibuan's (2005) statement that placement must be based on job descriptions and job specifications that have been determined and guided by the principle of the right person in the right place and the right person behind the work. An organization, according to Rivai (2004) Without support employees/employees who are suitable both in terms of quantitative, qualitative, strategic and operational aspects, then the organization/company will not be able to maintain its existence, develop and advance in the future. For this reason, quality human resources are needed to support the tasks that are the responsibility of the organization